The Profession of YouTuber: Ethics in the Islamic Economics’ Perspective - Tira Nur Fitria; Abdul Haris Romdhoni (Jurnal Ilmiah Ekonomi Islam, 2021)
One of the phenomenal businesses and professions in the world in the millennial digital world is as a YouTuber who can provide very promising benefits. Therefore, as a neutral, strategic, and preferred media, YouTuber videos have their important points that apart from being land for business. The objective of this research is to provide an understanding of the ethics of the YouTuber profession from the Islamic economics perspective. This research applies library research. The result shows that YouTube can be used as a means of conveying messages while remaining committed to the following Islamic ethics business, are: First, the video content is legal, lawful, and does not contain contradictory content in Islamic values, such as non-educational and other unsuitable content. The criteria for services being “traded” is lawful and valuable. Second, the products and advertising content in the video are halal and legal. These contents do not market products non-halal ads, conventional financial institutions, liquor, illegal goods, products that damage health, and products that destroy children's morals. Third, clarity of rights and obligations between the parties, including a YouTuber as a service seller and a company as a buyer of services carried out according to the agreement. Besides, there are other Islamic business ethics, namely: 1) principle of monotheism teaches that everything must reflect faith in Allah SWT and is responsible for all human actions including economic and business activities. 2) principle of justice teaches humans in every activity must be fair, both to themselves and others. Third, the principle of responsibility teaches that in every human activity, there is accountability to Allah SWT. Fourth, the principle of freedom teaches that every human has the freedom to choose and determine everything. Humans are given free will to control their lives alone, but must not ignore the fact that he is completely required by the law of God. Fifth, honesty and truth. Every activity, no matter how small, the activities carried out can be seen properly and feel good for others.